2009
DOI: 10.1182/blood-2008-07-168260
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of RUNX1 biallelic alteration in acute myeloid leukemia secondary to familial platelet disorder

Abstract: Familial platelet disorder (FPD),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 23 publications
3
141
0
1
Order By: Relevance
“…Four pathogenic or likely pathogenic variants were identified that are previously known to cause IT. These were found in patients; 54 ( GATA1 ; c.1240T>C, p.*414Arg+41), 59 ( RUNX1 ; c.386C>A, p.Ala129Glu), 70 ( GFI1B ; c.503G>T, p.Cys168Phe), and 64 ( MYH9 ; c.2152C>T, p.Arg718Trp) 3 , 15 , 16 , 17 …”
Section: Resultsmentioning
confidence: 95%
“…Four pathogenic or likely pathogenic variants were identified that are previously known to cause IT. These were found in patients; 54 ( GATA1 ; c.1240T>C, p.*414Arg+41), 59 ( RUNX1 ; c.386C>A, p.Ala129Glu), 70 ( GFI1B ; c.503G>T, p.Cys168Phe), and 64 ( MYH9 ; c.2152C>T, p.Arg718Trp) 3 , 15 , 16 , 17 …”
Section: Resultsmentioning
confidence: 95%
“…Three variants, ANKRD26; c.-126T>G in F2.I, MYH9; c.3493C>T (rs80338829) in F9.I and RUNX1; c.530G>A in F19.I and F19.II have been previously associated with IT. 1,19,20 The remaining three variants that have been previously observed occurred at frequencies of <0.005 (0.05%) in available databases. One of the databases scrutinized was that of the ExAC consortium (http://exac.broadinstitute.org) which may include data from individuals with low platelet counts who were either undiagnosed or recruited through an unrelated study (Table 2).…”
Section: Variants In Known Thrombocytopenia-causing Genesmentioning
confidence: 99%
“…One variant, RUNX1; p.Arg177Gln, observed in F19.I and F19.II has been previously reported as a causative germline mutation of a familial platelet disorder in two individuals from the same pedigree. 20 The variations consisted of five missense variants, two splice-site variants and one nonsense variant. One splice-site variation, c.270+1G>T, was present within three affected individuals from two separate families (F13 and F14).…”
Section: Variants In Known Thrombocytopenia-causing Genesmentioning
confidence: 99%
“…On the other hand, a high frequency of RUNX1 biallelic mutations in the patients with FPD/AML has been reported from a French group [42,43]. Besides RUNX1 biallelic mutations, a variety of mutations were identified at the AML stage, such as mutations in FLT3, KRAS, CBL, TP53, SRSF2, SF3B1, TET2, and DNMT3A [43].…”
Section: Additional Genetic Events For Mutant Clone Expansion and Leumentioning
confidence: 99%